2021
DOI: 10.1017/s0007114521003688
|View full text |Cite
|
Sign up to set email alerts
|

EPA and DHA confer protection against deoxynivalenol-induced endoplasmic reticulum stress and iron imbalance in IPEC-1 cells

Abstract: This study assessed the molecular mechanism of eicosapentaenoic acid (EPA) or docosahexaenoic acid (DHA) protection against IPEC-1 cell damage induced by deoxynivalenol (DON). The cells were divided into six groups, including the CON group, the EPA group, the DHA group, the DON group, the EPA+DON group, and the DHA+DON group. RNA sequencing was used to investigate the potential mechanism, and qRT-PCR was employed to verify the expression of selected genes. Changes in ultrastructure were used to estimate pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…In recent years, studies aimed at investigating the regulatory mechanisms underlying the effects of DON on pigs have predominantly focused on specific single organelles such as mitochondria and ER. , This has led to a limited understanding of the comprehensive regulatory network in response to the toxic effects of DON in piglets. Actually, organelles can interact with each other through the physical contacts between them such as the ERMCSs between mitochondria and ER, which was first discovered by Vance and has recently garnered increasing attention in the field of life science. , However, up to now, there is currently a lack of available data on the roles of ERMCSs involved in the intestinal health of piglets, except for one that we published earlier .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, studies aimed at investigating the regulatory mechanisms underlying the effects of DON on pigs have predominantly focused on specific single organelles such as mitochondria and ER. , This has led to a limited understanding of the comprehensive regulatory network in response to the toxic effects of DON in piglets. Actually, organelles can interact with each other through the physical contacts between them such as the ERMCSs between mitochondria and ER, which was first discovered by Vance and has recently garnered increasing attention in the field of life science. , However, up to now, there is currently a lack of available data on the roles of ERMCSs involved in the intestinal health of piglets, except for one that we published earlier .…”
Section: Discussionmentioning
confidence: 99%
“…14 Recently, it has been reported that ERS can be triggered by DON in intestinal porcine epithelial cell line 1 (IPEC-1). 7 However, little data have been reported about how ER was regulated in response to DON-induced intestinal injury in piglets.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when ER stress occurs, mRNA translation is disrupted, and protein misfolding increases, potentially leading to various intestinal diseases (Stengel et al., 2020). Several studies have demonstrated that DON induces ER stress in IPEC‐1 cells by upregulating the proportion of X‐Box Binding Protein 1s (XBP‐1s)/XBP‐1u, thereby exacerbating its cytotoxicity (Lin et al., 2022; Song et al., 2023). Similarly, FB 1 triggers ER stress and damages the intestinal epithelial barrier through CerS2 depletion in the IPEC‐J2 cell model (Li, Liu, et al., 2022).…”
Section: The Intestinal Toxicity Mechanism Of Foodborne Mycotoxinsmentioning
confidence: 99%